Rapid Determination of Cephalexin in Biological Media - O. I. Kulapina; A. M. Vostrikova (Антибиотики и Химиотерапия)
The behavior of cephalexin in pharmaceutical and biological media was studied by spectrophotometric method. The ranges of linearity and the limits of cephalexin detection were determined. The possibilities of spectrophotometric cephalexin determination in mixed saliva and in blood serum were shown. Optimal conditions of proteins precipitation were revealed. Pharmacokinetic parameters of cephalexin in oral fluid of patients with sinusitis were determined.